A survey of public elementary school libraries in Marikina City based on the standards set by the Department of Education, Culture and Sports - Torres, Maria Donavie B. (Institute of Library Science, University of the Philippines Diliman, 1998)
The Department of Education, Culture and Sports issued a bulletin pertaining to the minimum library standards recommended for elementary, secondary, and tertiary levels. This study was conducted to find out the state of public elementary school libraries in Marikina City, based on these set of standards. The fourteen schools included in this study were Barangka, Calumpang, Capitan Moy, Concepcion, Fortune, H. Bautista, Leodegario Victorino, Marikina, Nangka, Parang, San Roque, St. Mary, Sto. Nino, and Tanong Elementary School. These were assessed during the descriptive survey method. Data were gathered through questionnaires and interviews.